The effect of increasing compost rates on the yield and nutrient content of ryegrass (Lolium perenne L.) - Szabó, Anita (Acta Agraria Debreceniensis, 2012)
Satisfaction of the increasing needs of humanity causes large environmental load. To provide a livable environment for future generations we have to satisfy our needs with the use of sustainable management. This is one of the biggest challenges of nowadays. The amount of wastes emitted in increasing volume can be decreased by the recycling of them. The disposal of waste materials formed in the public spaces of cities and during the processing of agricultural row materials and by-products in landfills is inconceivable, so they must be recycled. These materials mostly with organic compounds could be the primary substrates of composts. Completed with suitable additives, and applied appropriate treating technology, composts are capable to supply horticultural plants with nutrients. Composting wastes and byproducts not just decreases the amounts of deposited waste materials, but increases the nutrient (macro- and micronutrients) content of soils, so this is an environmentally friendly and alternative way of nutrient management of plants.